2001
DOI: 10.1054/bjoc.2001.2165
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of sensitization of MDR cancer cells by Pluronic block copolymers: Selective energy depletion

Abstract: This paper, for the first time, demonstrates that exposure of cells to the poly(ethylene oxide)-poly(propylene oxide) block copolymer, Pluronic P85, results in a substantial decrease in ATP levels selectively in MDR cells. Cells expressing high levels of functional P-glycoprotein (MCF-7/ADR, KBv; LLC-MDR1; Caco-2, bovine brain microvessel endothelial cells [BBMECs]) are highly responsive to Pluronic treatment, while cells with low levels of P-glycoprotein expression (MCF-7, KB, LLC-PK1, human umbilical vein en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
208
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(223 citation statements)
references
References 18 publications
13
208
2
Order By: Relevance
“…However, such a system raises the problem of the integrity of the drug and the persistence of its cytotoxic activity (2). In addition, it was shown that block copolymer micelles decrease intracellular ATP levels together with reducing ATPase activity of P-glycoprotein (22,59). In all cases, a physical interaction between the structure of the nanocarrier and the efflux transporter itself has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a system raises the problem of the integrity of the drug and the persistence of its cytotoxic activity (2). In addition, it was shown that block copolymer micelles decrease intracellular ATP levels together with reducing ATPase activity of P-glycoprotein (22,59). In all cases, a physical interaction between the structure of the nanocarrier and the efflux transporter itself has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note is the evidence of antitumour activity of SP1049C in doxorubicin-resistant tumours (Batrakova et al, 1996) and in multiple drug resistance (MDR) cells (Venne et al, 1996;Alakhov et al, 1999). There appear to be several potential mechanisms, including inhibition of drug efflux transporters, abolishment of drug sequestration in acidic compartments, inhibition of the glutathione (GSH)/glutathione (GST) detoxification system and reduction of ATP selectively in MDR cells (Venne et al, 1996;Batrakova et al, 2001;Kabanov et al, 2002). In preclinical models, in vivo SP1049C was found to be superior to convential doxorubicin in all nine models tested.…”
Section: Discussionmentioning
confidence: 99%
“…7 The monoclonal antibodies to Pgp, C219 (Dako Corp., Carpinteria, CA), were used at 1:100 dilution. The monoclonal antibodies to β-actin, anti-β-1-chicken integrin (Sigma, Inc.), were used at 1:200 dilution.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…8 In addition Pluronic induces intracellular ATP depletion in MDR cells thus depriving these cells from the source of energy necessary for the function of Pgp and other cellular defense mechanisms. 7 The synergy between these two effects results in the strong chemosensitization of MDR tumors. The use of Pluronic in chemotherapy of the MDR tumors has reached clinical evaluation stages.…”
Section: Introductionmentioning
confidence: 99%